The roles of triglyceride/high-density lipoprotein cholesterol ratio and uric acid as predisposing factors for metabolic syndrome in healthy children - Maria Efthymia Katsa; Anastasios Ioannidis; Athanasios Sachlas; Ioannis Dimopoulos; Stylianos Chatzipanagiotou; Andrea Paola Rojas Gil (Korean Society of Pediatric Endocrinology, 2019)
Purpose To estimate the roles of triglyceride/high-density lipoprotein cholesterol (TG/HDL) ratio and uric acid in predisposition for metabolic syndrome (MetS) and its components in healthy children. Methods Anthropometric and biochemical analyses were performed on 110 children, aged 5 to 12 years, from the Greek county of Laconia. The children were studied as a whole population and in separate groups according to age and predisposition to MetS after taking into consideration International Diabetes Federation criteria, body mass index, and lipid profile. Results Seventeen percent of children exhibited predisposition to MetS, while 39.1% had TG/HDL ratio >1, and 3.64% had high level of uric acid. According to a receiver operating characteristic curve analysis, the relative probability for MetS predisposition sextupled when TG/HDL ratio was ≥1 (odds ratio [OR], 5.986; 95% confidence interval [CI], 1.968-18.205). Children in the total population and those aged < 9 years had a greater probability for increased low-density lipoprotein (LDL) cholesterol (OR, 3.614; 95% CI, 1.561-8.365) when TG/HDL ratio was ≥ 1. The TG/HDL ratio was positively correlated with body mass index (BMI) (P=0.035) in children without MetS, cholesterol in the total population (P=0.06) and children ≥9 years old (P=0.026), and with LDL in the total population and both age groups (P=0.001). The TG/HDL ratio was also positively correlated with alanine aminotransferase in the total population (P=0.033) and gamma-glutamyl transferase in most studied groups (P<0.001). Uric acid was positively correlated with waist circumference in the total population (P=0.043) and in those without MetS (P=0.027). It was also positively correlated with BMI, TG, cholesterol, and TG/HDL ratio and negatively correlated with HDL in most studied groups (P<0.005). Conclusions The studied parameters correlated with MetS components and could be characterized as effective indexes for childhood MetS, regardless of age and predisposition to MetS.